Effect of type 1 piliation on in vitro killing of Escherichia coli by mouse peritoneal macrophages. - Keith, B R (1990)
Escherichia coli K-12 mutants possessing defined lesions affecting type 1 pilus production, receptor binding, or length were examined for their ability to resist killing by mouse peritoneal macrophages in vitro. Mutants were mixed pairwise at known ratios in wells containing macrophages, and after incubation, the ratio of the survivors was assayed. The difference in phagocytic killing between type 1 piliated cells and isogenic nonpiliated cells was significant, the piliated cells being approximately threefold more resistant. Pilus length had little effect upon survival, as the long-piliated mutants were no more resistant to killing than the normal-length parents. Interestingly, the receptor-binding function of type 1 pili was most important in effecting resistance, as mutants lacking the ability to bind receptor were killed as effectively as nonpiliated mutants. These data are consistent with the notion that pili actually impede killing by macrophages rather than serve as passive physical barriers to uptake.